Analysis of the Influence of Internal Audit and Whistleblowing System on Fraud Prevention - Firdausi, Qonita; Kurniawan, Sunny Agung; Agusiady, Raden Ricky (Golden Ratio of Finance Management, 2024)
This research aimed to comprehensively determine and analyze internal audit and whistleblowing systems in the context of fraud prevention efforts. A research design using qualitative descriptive analysis and a literature review approach was used. Data was collected in journals or scientific articles, as many as 10 articles from journal provider websites, from 2019 - 2024. Based on the analysis of 10 articles, six articles state that internal audit has a significant influence on fraud prevention efforts. The data analysis supports this finding results from several studies showing a positive and significant correlation between the role of internal audit and fraud prevention efforts. Then, four research articles do not explain the influence of internal audit. The study's results, based on 10 articles and nine research articles, state that the whistleblowing system positively influences fraud prevention efforts.